TINDAK PIDANA KEKERASAN FISIK OLEH SUAMI YANG TIDAK MENGHALANGI PEKERJAAN RUMAH TANGGA (PUTUSAN NOMOR 54/PID.B/2023/PN TGT): The Crime of Physical Violence by a Husband that Does Not Obstruct Domestic Work (Court Decision Num.54/Pid.B/2023/PN Tgt) - Albina Aristin Siburian; Azmi Syahputra (Faculty of Law, Universitas Trisakti, 2025)
Komnas Perempuan reported an increase in domestic violence by almost 10 percent in 2024 compared to 2023. The most common form of violence is sexual violence. General data on the total number of cases of violence against women is 445,502 cases. The problems studied are: Is the decision of the Tanah Grogot District Court Number 54/Pid.B/2023/PN Tgt which found the defendant guilty of committing the crime of Article 44 paragraph (1) of Law No. 23 of 2004 concerning the Elimination of Domestic Violence (hereinafter abbreviated as UUPKDRT) appropriate? The research method used, namely normative juridical, especially research on legal principles, is descriptive, the data type uses secondary data, and the conclusion uses deductive logic. This research result and concludes that the court's decision in the case which applied Article 44 paragraph (1) of the Domestic Violence Law was inappropriate. However, the provisions of Article 44 paragraph (4) are more appropriate to be applied because they fulfill all the necessary elements. This is based on the fact that the act's impact on the victim did not interfere with the victim's daily activities.